2022
DOI: 10.2196/34279
|View full text |Cite
|
Sign up to set email alerts
|

Application of Spatial Risk Assessment Integrated With a Mobile App in Fighting Against the Introduction of African Swine Fever in Pig Farms in Thailand: Development Study

Abstract: Background African swine fever (ASF), a highly contagious disease affecting both domestic and wild pigs, has been having a serious impact on the swine industry worldwide. This important transboundary animal disease can be spread by animals and ticks via direct transmission and by contaminated feed and fomites via indirect transmission because of the high environmental resistance of the ASF virus. Thus, the prevention of the introduction of ASF to areas free of ASF is essential. After an outbreak wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…Similarly, in January 2022, the Italian continent also notified the occurrence of ASFV genotype II after an absence of about 40 years ( Beato et al, 2022 ; Iscaro et al, 2022 ). Meanwhile, two new countries have been affected: one of two in North Macedonia, caused by farms that were predominantly small-scale with high rates of turnover and the highest frequency of wild boar sightings ( O’Hara et al, 2021 ), and the other of two in Thailand, caused by infected live and dead pigs, pork products, and wild boar semen, contaminated feed, and fomites ( Thanapongtharm et al, 2022 ). The first reported ASF occurrence in Nepal was in March 2022, although the government had already banned the import of pigs and pork products from countries infected with ASFV on January 28, 2019 ( Acharya and Wilson, 2020 ; Figure 1 ).…”
Section: Global Scenario and Prevalence Of Asfmentioning
confidence: 99%
“…Similarly, in January 2022, the Italian continent also notified the occurrence of ASFV genotype II after an absence of about 40 years ( Beato et al, 2022 ; Iscaro et al, 2022 ). Meanwhile, two new countries have been affected: one of two in North Macedonia, caused by farms that were predominantly small-scale with high rates of turnover and the highest frequency of wild boar sightings ( O’Hara et al, 2021 ), and the other of two in Thailand, caused by infected live and dead pigs, pork products, and wild boar semen, contaminated feed, and fomites ( Thanapongtharm et al, 2022 ). The first reported ASF occurrence in Nepal was in March 2022, although the government had already banned the import of pigs and pork products from countries infected with ASFV on January 28, 2019 ( Acharya and Wilson, 2020 ; Figure 1 ).…”
Section: Global Scenario and Prevalence Of Asfmentioning
confidence: 99%
“…In a spatial risk assessment study of ASF introduction in Thailand, distance from the border was identified as one of the highest-priority risk factors. Consequently, several ASF outbreaks are now reported in many of these land-bordering areas ( 140 ). All frequently used distribution routes, not just road transportation networks, require attention.…”
Section: Asf Subregional Update In Southeast Asiamentioning
confidence: 99%
“…Moreover, in the past twenty years, there have been numerous transboundary emerging disease outbreaks among domestic animals in Thailand. For example, there have been outbreaks of lumpy skin disease among cattle (31), African horse sickness among horses (32), and African swine fever among pigs (33). Hence, it is crucial to investigate where there are high risk areas to prevent disease transmission to wild populations, considering their susceptibility to similar pathogens shared by livestock.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic diseases like bovine tuberculosis and brucellosis with long incubation and relatively low fatality rates could potentially have long-term consequences by reducing populations due to disease, while FMD, which has a higher transmission rate with short incubation periods or even highly fatal infections such as anthrax, may have lower impacts on populations (30) Moreover, in the past twenty years, there have been numerous transboundary emerging disease outbreaks among domestic animals in Thailand. For example, there have been outbreaks of lumpy skin disease among cattle (31), African horse sickness among horses (32), and African swine fever among pigs (33). Hence, it is crucial to investigate where there are high risk areas to prevent disease transmission to wild populations, considering their susceptibility to similar pathogens shared by livestock.…”
Section: Introductionmentioning
confidence: 99%